Wayfinding e legibilidade ambiental em parque urbano: um estudo da percepção de usuários idosos - Nogueira, Dhyego de Lima (2017)
This research aimed to evaluate the environmental perception of the elderly in an urban park of João Pessoa-PB, identifying elements of spatial legibility and how they contribute to wayfinding process. Wayfinding was chosen as the conceptual basis to allow understanding of navigability by the user as part of the articulation and spatial orientation. The concept of legibility, by Kevin Lynch (1960/1997), will allow the elderly user to understand the clarity of the urban landscape as well the analyzed environment. The research had as a case study the Zoobotanical Park Arruda Câmara, also known as “Parque da Bica”. The methodology had a multi-method approach used in the person-environment relationship, and aimed to observe and analyse the environment and the elderly users. The environment was verified from documentary survey, exploratory visits and walkthrough. With the users, behavioral maps focused on the individual were conducted, structured interviews and guided tours with associated orientation strategies. These strategies used with the elderly aimed to identify the spatial and environmental perception about which aspects would make the spatial orientation easier or harder and displacement by the environment considering ways of orientation, decision making, environmental accessibility, environmental infrastructure, among others. From the results it was possible to identify faults in the infrastructure of the Park that can influence the way the elderly perceives guided by Bica Park. Spaces of low traffic of elderly or that did not present signage, were not used for fear or for not demonstrating motivation for visitation. Aspects related to the lack of spatial reference or inadequacies in informative and directional manner, such as precarious maintenance routes and inadequate stairs and ramps have generated barriers for displacement, demonstrating aspects of legibility that could difficult the wayfinding process. It was also identified that the elderly perceived the Park positively, however, they believed and referred to the need for improvements to facilitate access, use, displacement and security of this public and, especially, those users with some degree of limitation or disability, or those who have low schooling. Finally, it is considered that methodological strategies used demonstrated efficacy to establish a more accurate look at the elderly perception and how environmental legibility helped in the process of wayfinding in the Park in question.